Impact of integrated STEM smart communities program on students scientific creativity - Rasul, Mohamad Sattar; Zahriman, Norsalehan; Halim, Lilia; Abd Rauf, Rose Amnah (Taylor's University, 2018)
Scientific creativity is such a complex skill and is often ignored by teachers during teaching activities. The purpose of this study was to identify students’ changes of scientific creativity in an integrated STEM of Smart Communities programme. The programme exposed students with integrated STEM education through project-based learning involving the application of the engineering design process. The elements of scientific creativity are divided into three aspects, which are scientific processes, inquiry skills, and creative thinking. The study was conducted experimentally on two groups of students, i.e., the control group that did not receive the STEM of Smart Communities modules and the treatment group, i.e., students who had received the modules. This study was conducted in six schools, with three schools with an intervention and three schools without any intervention. Data were collected through a questionnaire given to 330 students. The findings showed a significant difference and have a positive impact on the element of scientific processes, inquiry skills and creative thinking among students with interventions rather than students without intervention.